Ixekizumab is efficacious when used alone or when added to conventional synthetic disease-modifying antirheumatic drugs (cDMARDs) in patients with active psoriatic arthritis and previous inadequate response or intolerance to tumour necrosis factor inhibitors - Peter Nash; Frank Behrens; Ana-Maria Orbai; Suchitrita S Rathmann; David H Adams; Olivier Benichou; Atul Deodhar (RMD Open)
Objective To conduct subset analyses of SPIRIT-P2 (NCT02349295) to investigate the efficacy and safety of ixekizumab versus placebo in three subgroups of patients with active psoriatic arthritis (PsA) according to the concomitant conventional synthetic disease-modifying antirheumatic drug (cDMARD) received: any background cDMARDs (including methotrexate), background methotrexate only, or none.Methods Patients were randomised to receive placebo, ixekizumab 80 mg every 4 weeks (IXEQ4W) or every 2 weeks (IXEQ2W). Efficacy and safety were assessed when patients were subdivided according to cDMARD use at baseline. Efficacy was evaluated versus placebo at week 24 by the American College of Rheumatology criteria (ACR20/50), achievement of minimal disease activity (MDA) state, Disease Activity Index for PsA (DAPSA), 28-joint Disease Activity Score using C-reactive protein (DAS28-CRP), Health Assessment Questionnaire-Disability Index and the 36-item Short-Form health survey physical functioning domain.Results Regardless of background cDMARD status, ACR20, ACR50 and MDA response rates were significantly higher than placebo with IXEQ4W or IXEQ2W treatment. Similarly, significant improvements were observed relative to placebo for DAS28-CRP and DAPSA across subgroups. Physical function also significantly improved relative to placebo with IXEQ4W treatment regardless of background cDMARD status and with IXEQ2W alone. Percentages of reported treatment-emergent adverse events (AEs), serious AEs (including serious infections) and discontinuations due to AEs in each subgroup were comparable to the overall SPIRIT-P2 population.Conclusion Ixekizumab was efficacious in patients with active PsA and previous tumour necrosis factor inhibitor (TNFi) inadequate response or TNFi intolerance treated with ixekizumab alone or when added to cDMARDs with subgroup safety profiles that were consistent with that observed in the overall SPIRIT-P2 population.